Physical Activity, Sedentary Behaviour, and Diet in Menopausal Women: Comparison Between COVID19 “first wave” and “second wave” of pandemic in Italy - Coppi, Francesca; Nasi, Milena; Farinetti, Alberto; Manenti, Antonio; Gallina, Sabina; Mattioli, Anna Vittoria (Progress in Nutrition, 2021)
The COVID-19 pandemic has strongly affected young population all over the world. The present study explores the effects of COVID-19 on physical activity, sedentary behaviour, and diet in a population of 435 menopausal women during the first phase of the pandemic (so-called the "first wave") and during the second spread of infections, after the summer release (so-called "second wave"). Women reported an increase in perceived stress and emotional distress which led to an increase in amount of food (42%), an increase in the consumption of snacks and junk food (48%) and to a switch to an unhealthy diet (46%) and weight gain in 51% of subjects. Most women stopped any physical activity, including outdoor walking, except for a small group (54 = 12%) who continued exercising at home. Unexpectedly, the second wave led to similar results as the first wave. Despite the increase in knowledge about the virus, therapies and the rapid development of vaccines to contain the spread of the disease, fear, stress and anxiety have not diminished as expected. In conclusion, the adoption of an unhealthy lifestyle during the pandemic and the persistence of these behaviors has determined and will cause important damage to the health of women in menopause, in particular an increase in obesity and related metabolic diseases is expected